“REFORMA AL CÓDIGO ORGÁNICO INTEGRAL PENAL RESPECTO A LA PROPORCIONALIDAD DE LA PENA, EN LOS DELITOS CONTRA LA FLORA Y FAUNA SILVESTRES” - Ortiz Huaca, Shirley Adeliz (2021)
This thesis entitled: "Reform of the Comprehensive Organic Penal Code, regarding the proportionality of the penalty in crimes against wild flora and fauna", refers to a social and legal problem with great relevance, which must be subject to interpretation and changes in the legal regulations that currently determine it, such as the Comprehensive Organic Criminal Code, specifically Article 247, which refers to crimes against wild flora and fauna, which in Ecuador this type of threatening acts are of great significance due to the high increase in cases that injure wildlife, and although this article determines a penalty of deprivation of liberty, it is not being sufficient and in accordance with the Constitution, International Instruments, and, to the damages suffered by many species and Nature product of these crimes. That is why the need to reform the penalty established by a stricter and more proportional one in the Comprehensive Organic Criminal Code. It is necessary to resort to legal means that protect the rights of wild flora and fauna as enshrined in the Constitution of the Republic of Ecuador in article 10 where it determines that Nature is subject to rights, therefore, it cannot be violated. , a fact that is considered important in the evolution of the preservation of Nature, as is determined by articles 14 and 71 of the same legal norm on the protection and validity of these rights, so that society learns to live in harmony with Nature, without damaging the life, integrity, evolution of its life processes for any reason. From there also derives the responsibility of the State to offer effective justice in criminal matters where those rights and legal rights that are criminally protected against any act that injure the life of wild species are debated. By virtue of what is determined in International Instruments, the defense and protection to reduce this type of crimes is extremely demanding that they point to where the legislations of the 5 member countries should focus, issuing principles, appendices, provisions so that the States can guide and intensify themselves to preserve, conserve, and help protect wild flora and fauna. In the comparative legislation, it was possible to show that they establish custodial penalties of no less than three years, which is why it grants a limit of freedom by strictly imposing the law, this is with the benefit of sustaining and preserving the biodiversity they possess. It is also necessary to mention the study techniques used, which were of great help such as the survey, interview, and documentary observation, the same that served as a basis to solve the investigation, in the same way the methods used that served as guide among them: Scientific, Inductive, Deductive, Analytical, Comparative, Historical, Mayeutic. From the above, the problem that exists in society and in Ecuadorian legal norms is evident, in addition to the fact that the Government has to prioritize Nature and its species more, therefore, it is of vital importance that a legal reform be carried out in the Organic Code Comprehensive Penal, eradicating all kinds of violence that threatens wild flora and fauna and their constitutional rights.